Who killed Lindbergh's baby? [videorecording (DVD)] - Klein, Larry; Klein, Larry; Klein, Larry; Sanders, Jay O., 1953-; Douglas, John E.; Haas, Paula; Falzini, Mark W. (PBS : Distributed by PBS Distribution, 2013)
Presents new forensic evidence in the Lindbergh kidnapping case, calling into question the verdict that the crime had been committed by German immigrant Bruno Hauptman. Includes theories by FBI criminal profiler John Douglas.